Probiotic properties of exopolysaccharides-producing Lactobacillus isolated from tempoyak - Suliman, Eilaf Suliman Khalil; Abd Manap, Mohd Yazid; Mustafa, Shuhaimi; Alhelli, Amaal Mohammed; Shokryazdan, Parisa (MDPI, 2018)
Tempoyak is a functional Malaysian food (an acid-fermented condiment) which is produced from the pulp of the durian (Durio zibethinus) fruit. The current study aimed to isolate and identify potential exopolysaccharide (EPS)-producing Lactobacillus strains from tempoyak for potential use as probiotics. Seven isolates (DUR2, DUR4, DUR5, DUR8, DUR12, DUR18, and DUR20) out of 44 were able to produce EPS, and exhibited resistance to acid and bile salt compared to the reference strains Lactobacillus rhmnosus (ATCC53103) and L. plantarum (ATCC8014). The seven isolated strains belonged to five different species—L. plantarum, L. fermentum, L. crispatus, L. reuteri, and L. pentosus—which were identified using API 50 CHL and 16S rRNA gene sequences (Polymerase chain reaction, PCR – based). The seven strains displayed different ability to produce EPS (100–850 mg/L). Isolates exhibited a high survivability to acid (pH 3.0), bile salts (0.3%), and gastrointestinal tract model (<70%). Results showed that the auto-aggregation and cell surface hydrophobicity ranged from 39.98% to 60.09% and 50.80% to 80.53%, respectively, whereas, the highest co-aggregation value (66.44%) was observed by L. fermentum (DUR8) with Pseudomonas aeruginosa. The isolates showed good inhibitory activity against tested pathogens, high antioxidant activity (32.29% to 73.36%), and good ability to reduce cholesterol (22.55% to 75.15%). Thus, the seven tested strains have value as probiotics.